P-29 Implementation strategies and research of advance care planning in nursing homes. An integrative, systematic review of the literature. (1st September 2015) - Flo, E; Bruusgaard, P; Husebø, Bettina S; Gjerberg, E; Thoresen, Lisbeth; Pedersen, R
Abstract : Background: Nursing home (NH) patients have complex health problems, disabilities and needs for Advance Care Planning (ACP). No previous reviews have investigated the methods and strategies for implementation of ACP in NHs. Aim: This systematic review investigates methods, design and outcomes and the implementation of ACP (i.e., themes and guiding questions, setting, facilitators, implementers, and promoters/barriers). Methods: A search using ACP MESH-terms and key words were conducted in CINAHL, Medline, PsychINFO, Embase and Cochrane libraries. We excluded studies on home-dwelling and hospital patients; only including specific diagnoses and/or chart-based interventions without conversations. Results: 16 papers were included. There were large variations in definitions and content of ACP, study design, implementation strategies, and outcomes. Often the ACP or implementation processes were not described. Few studies included patients lacking decision-making capacity – who are numerous in most nursing homes. The chief ACP implementation strategy was education of staff. Among others, ACP improved documentation of and adherence to preferences. Important implementation barriers were non-attending NH physicians, legal challenges and reluctance to participate among personnel and relatives. Discussion: Variation in ACP definitions may be related to cultural and legal differences. This variation, together with sparse  information about procedures, makes collation and comparison of research results challenging. Conclusion: ACP intervention studies in NH are few and heterogenous. Key information is sometimes lacking. Thus, comparing results and replicating studies is challenging. Essential implementation considerations relate to the involvement and education of nurses, physicians and leaders.